Peran Struktur Modal dan Likuiditas terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening pada Sektor Transportasi - Fina Putri Handayani; Ariati Anomsari; Agus Prayitno; Suhita Whini Setyahuni (Pusat Riset dan Inovasi Nasional, 2026)
The objective of this study is to evaluate the impact of capital structure (DER) and liquidity (CR) on company value (PBV) in the transportation sector listed on the Indonesian Stock Exchange (IDX) during the period 2019-2024 and to analyze the role of return on assets (ROA) as a mediating variable. This study used panel data regression analysis using EViews 13 software. The study population consisted of 62 companies in the transportation sector whose shares are listed on the Indonesian Stock Exchange. The sample consisted of 26 companies selected through purposive sampling. The study period was 2019-2024. This study demonstrates that DER and CR have no effect on ROA. Furthermore, it found that DER and CR significantly affect PBV, while ROA has no effect. Sobel testing also showed that ROA does not mediate the impact of DER and CR on PBV. The novelty of this study lies in its finding that profit does not play a mediating role between financial structure and liquidity that affects a company’s market value. The study results indicate that financial structure and liquidity management play a more significant role than profit in increasing company value in the transportation sector. Therefore, these may be key factors for managers and investors in making financial decisions.